Syngenetic dynamic of permafrost of a polar desert solifluction lobe, Ward Hunt Island, Nunavut - Verpaelst, Manuel; Fortier, Daniel; Kanevskiy, Mikhail; Paquette, Michel; Shur, Yuri (NRC Research Press (a division of Canadian Science Publishing), 2017)
Repeated freeze-thaw cycles on slopes trigger sorting and solifluction mass movements, while subsequent displacement of material modifies the geomorphology of slopes as well as permafrost dynamics. This study focuses on the geomorphology and the cryostratigraphy of a polar desert stone-banked solifluction lobe with the objective to clarify the impact of slow mass movements on ground ice aggradation. The morphology of the solifluction lobe was characterized by peripheral ridges of coarse gravel, partially surrounding a depression filled with finer sediments saturated with water and covered by organics. Cryostratigraphic analysis demonstrated that the solifluction lobeâ s formation lead to the development of a syngenetic layer of permafrost with an ice content that varied according to the location in the lobe. The ice-rich cryofacies formed in the central depression of the lobe should act as a buffer to potential active layer deepening, slowing down its thawing, whereas the ice-poor cryofacies formed under the ridges is expected to thaw faster than the central depression under climate warming scenarios. Thawing of the ice-rich zone in the future will result in differential thaw subsidence between the ridges and the central depression of solifluction lobes, along with increased drainage through the ridges and subsequent changes in hydrology. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.